2013
DOI: 10.1371/journal.pone.0068614
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GSK 3β Activity Is Associated with Excessive EZH2 Expression and Enhanced Tumour Invasion in Nasopharyngeal Carcinoma

Abstract: BackgroundEnhancer of zeste homolog 2 (EZH2) has been shown to contribute to tumour development and/or progression. However, the signalling pathway underlying the regulation of EZH2 in nasopharyngeal carcinoma (NPC) remains unclear. Since EZH2 contains the putative Glycogen synthase kinase 3 beta (GSK3β) phosphorylation motif ADHWDSKNVSCKNC (591) and may act as a possible substrate of GSK-3β, it is possible that inactivation of GSK3β may lead to excessive EZH2 expression in NPC.MethodWe first examined the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Overexpression of EZH2 is a marker of advanced and metastatic disease in many solid tumors, including prostate cancer and NPC [18]. Previously, we reported that EZH2 expression was significantly enhanced in NPC tissues, which was regulated by GSK-3β [16]. In this study, we found that EZH2 expression was significantly associated with the TNM stage of NPC, suggesting that EZH2 may play a critical role in the progression of NPC.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Overexpression of EZH2 is a marker of advanced and metastatic disease in many solid tumors, including prostate cancer and NPC [18]. Previously, we reported that EZH2 expression was significantly enhanced in NPC tissues, which was regulated by GSK-3β [16]. In this study, we found that EZH2 expression was significantly associated with the TNM stage of NPC, suggesting that EZH2 may play a critical role in the progression of NPC.…”
Section: Discussionsupporting
confidence: 52%
“…Immunohistochemical staining was performed as previously reported [16]. Briefly, human tissue sections were stained for the expression of OPN (1:200) and EZH2 (1:200; Cell Signalling, Danvers, Mass., USA) and detected by streptavidin-biotin-horseradish peroxidase complex formation (Zhongshanjinqiao, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These patterns are widespread and have great biological significance [96]. Excessive EZH2 expression by the inhibition of GSK-3β activity enhances NPC tumor invasion [100]. The overexpression of BRD7 inhibits NPC cell growth and the cell cycle by transcriptional regulation, which is achieved by BRD7 binding to lysine-acetylated peptides derived from histone H3 with K9 or K14 acetylated and from histone H4 with K8, K12, or K16 acetylated.…”
Section: Histone Modifications In Npcmentioning
confidence: 99%